Relapsing drug-induced hypersensitivity syndrome. Issue 4 (August 2016) - Tan, Sze-Chin; Chan, Grace Y.L.
Abstract : Purpose of review: Drug-induced hypersensitivity syndrome (DIHS) is a serious adverse drug reaction with potential morbidity and mortality. 'Flare up' or relapses in DIHS is a rare but important feature. These relapses may occur within days to several weeks, even after discontinuation of the offending drug. In this article, we review the pathogenesis of DIHS, implication of human herpesvirus 6 reactivation, and describe published case reports of patients with relapsing DIHS. Recent findings: Common drugs associated with DIHS include (but are not limited to) antiepileptics such as carbamazepine, phenytoin, and valproic acid; antituberculous drugs; sulfasalazine; allopurinol; and antivirals such as abacavir and nevirapine. Relapses may occur even after cessation of the culprit drug and appropriate management with corticosteroids. Studies have suggested that reactivation of herpesvirus, particularly, human herpesvirus 6, is the main cause of relapses. However, other pathomechanisms have been proposed – case reports have described the importance of drug cosensitization. In such cases, the introduction of a second drug (often an antibiotic) induces the relapse of DIHS. DIHS may also cause multiple drug allergies, where a patient develops sensitisation to other drugs which were previously well tolerated. Summary: Large studies are lacking in this heterogeneous condition. More research is needed to further understand the pathogenesis of drug cosensitization and multiple drug allergies, role of genetics, identification of risk factors, and prevention of relapses in DIHS.